O11.5 Risks For Sexually Transmitted Infections (STIs), HIV, and Pregnancy Among Women Working in Entertainment Establishments in Cambodia. (13th July 2013) - Killam, W P; Mun, P; Mutuc, J D; Chann, N; Chan, S; Shiraishi, R W; Warren, D; Vun, M C
Abstract : Background: Since the 1990s, Cambodia successfully reduced HIV and STI prevalence among female sex workers. In 2008, brothels were outlawed, and non-brothel Entertainment Establishments (EEs) increased. Some women working in EEs exchange sex for gifts or money. We examined associations between behavioural risks and STIs, HIV and pregnancy among Cambodian Female Entertainment Workers (FEWs). Methods: In 2011, a stratified multi-stage cluster survey of 2, 564 FEWs was conducted in karaoke establishments, beer halls, and former brothels. Participants consented to private interviews, blood collection, and self-administered vaginal swabs for gonorrhoea and chlamydia. Analyses were weighted and controlled for the complex design of the survey. Logistic regression models were used to examine potential risk factors of STIs, HIV and pregnancy. Results: Transactional sex in the last year was reported by 41.1% of FEWs. Chlamydia (18.9%), gonorrhoea (5.3%), and active syphilis (0.4%) were associated with younger age (p < 0.0001). HIV (2.6%) and pregnancies (n = 1194) were more likely among older women (p < 0.0001). Heavy drinking was associated with gonorrhoea (odds ratio [OR] = 2.5, 95% CI 1.1–5.4), while drug use was associated with any STI (p = 0.0062) and HIV (p = 0.0005). Always using condoms varied by partner type (clients [74.0%], boyfriends [31.2%], and husbands [9.8%]) and was negatively associated with pregnancy only. Working in a former brothel (OR = 2.5, 95% CI 1.4–4.6) and having > 7 vs. ≤ 7 clients per week (OR = 3.8, 95% CI 1.8–7.7) was associated with HIV. Among FEWs, 36.8% had clients plus a husband and/or boyfriend. Those with both a boyfriend and client had the highest odds of any STI (OR = 3.8, 95% CI 2.2–6.7). Conclusion: Cambodian FEWs are a heterogeneous group with varying risk behaviours. STIs and HIV appear to be concentrated in distinct subpopulations, but sexual partner relationships contribute to the complex transmission dynamics. Defining those most at risk will help focus national prevention and case-finding programmes.